Pemberdayaan ekonomi perempuan melalui pengembangan Industri Rumah Tangga (IRT) Rengginang - Arlinda Arlinda; Denayu Grandis; Desi Ika Sari; Dian Dwi Lestari; Elsa Firda Yustika; Elya Kurniawati (Universitas Negeri Malang, 2021)
The era of industrialization is currently growing rapidly in the economic field. The rapid development of an industrial center is undeniable, of course, requiring workers to support the optimization of products that will be offered. Starting with the existence of home industries, in the sense that the industry is covered on a small scale and capital that is not too large. In addition, because it is usually only done in a home environment, it is also possible to attract the interest of the surrounding community. One of them is the home industry of Rengginang in Sambigede village, Sumberpucung sub-district. This study wanted to know the economic empowerment of women through the development of rengginang IRT in Sambigede village, using qualitative research methods and 4 research subjects namely 2 women IRT owners and 2 female laborers in the Rengginang IRT, and this study used the Functional Talcot Parson theory. Rengginang home industry in this village is an effort to empower women by helping previously unemployed housewives to work at home, with the aim of helping to increase income in their families. With this, it can be concluded from this study that 1) the rengginang IRT in Sambigede village is not only 1 but there are several IRTs in Sambigede village, 2) the majority of workers who work at the Rengginang IRT are housewives who live in the village Sambigede, and 3) The Rengginang IRT in Sambigede has been running for a long time and has been passed down from generation to generation. Era industrialisasi saat ini semakin berkembang pesat dalam bidang perekonomian. Berkembang pesatnya suatu sentra industri tidak dipungkiri tentu membutuhkan pekerja untuk menopang optimalisasi produk yang akan ditawarkan. Dimulai dengan adanya industri rumah tangga, dalam artian industri tersebut tercakup dalam skala yang kecil serta modal yang tidak terlalu besar. Selain itu karena biasanya hanya dilakukan di lingkup rumahan, sehingga dimungkinkan pula akan menarik minat masyarakat sekitar saja. Salah satunya yakni industri rumah tangga Rengginang desa Sambigede, kecamatan Sumberpucung. Penelitian ini ingin mengetahui pemberdayaan ekonomi perempuan melalui pengembangan IRT rengginang di desa sambigede, dengan menggunakan metode penelitian kualitatif dan subjek penelitian berjumlah 4 orang yaitu 2 wanita pemilik IRT dan 2 wanita buruh dalam IRT rengginang, dan penelitian ini menggunakan teori struktural Fungsional Talcot Parson. Industri rumah tangga rengginang di desa ini merupakan upaya pemberdayaan wanita dengan membantu para ibu rumah tangga yang sebelumnya menganggur dapat bekerja di rumah, dengan tujuan membantu menambah pendapatan di keluarganya. Dengan hal tersebut dapat disimpulkan dari penelitian ini yaitu 1) IRT rengginang di desa sambigede ini bukan hanya 1 namun ada beberapa IRT yang ada di desa sambigede, 2) mayoritas buruh yang bekerja di IRT rengginang merupakan ibu – ibu rumah tangga yang bertempat tinggal di desa sambigede, dan 3) IRT rengginang di sambigede ini berjalan sudah sejak lama dan secara turun temurun.